Perianal pruritus in dogs with skin disease. Issue 3 (5th May 2014) - Maina, Elisa; Galzerano, Mario; Noli, Chiara
Abstract : Background: Perianal pruritus has been reported in dogs with anal sac disease but not in healthy dogs. Some authors describe it as typical of allergy, but there is little evidence in support of this. Hypothesis/Objectives: The aim was to investigate the association between perianal pruritus and canine atopic dermatitis (CAD), adverse food reaction (ARF) and other skin diseases in dogs. Animals: Two hundred and fifty privately owned dogs with skin disease and without anal sac disease. Methods: The presence or absence of perianal pruritus, macroscopic and cytological evaluation of the perianal skin surface and the macroscopic appearance of anal sac contents were assessed. Chi‐square and Fisher's exact tests were performed to compare the frequency of perianal pruritus with the clinical diagnoses and with clinical and cytological parameters. Results: Perianal pruritus was seen in 39 of 75 dogs with CAD, in 29 of 57 dogs with ARF and in only 24 of 118 dogs with other conditions. The frequency of perianal pruritus in dogs with CAD and/or ARF was significantly higher than that in dogs with other diagnoses ( P <  0.0001). No other disease was significantly associated with perianal pruritus. Perianal pruritus was significantly associated with signs of perianal alopecia, erythema, excoriations, lichenification and hyperpigmentation; it was not associated with the presence of bacteria or yeasts or with anal sac impaction. Conclusions and clinical importance: Perianal pruritus was seen more frequently in dogs with AFR/CAD than with other dermatological diseases. This is the first study to evaluate perianal pruritus in dogs with skin disease and without anal sac disease. Abstract : Background‐ Perianal pruritus has been reported in dogs with anal sac disease but not in healthy dogs. Some authors describe it as typical of allergy, but there is little evidence in support of this.Hypothesis/Objectives‐ The aim was to investigate the association between perianal pruritus and canine atopic dermatitis (CAD), adverse food reaction (ARF) and other skin diseases in dogs.Conclusions and clinical importance‐ Perianal pruritus was seen more frequently in dogs with AFR/CAD than with other dermatological diseases. This is the first study to evaluate perianal pruritus in dogs with skin disease and without anal sac disease.